Enriching English vocabulary of young learners by using the “Word Guess” game and flashcard media - Utami, Irma Fajar Tri; Lestari, Titis Yekti; Rosyta, Merie Dreana Kamelia; Indriani, Lilia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to introduce English to young learners by enriching their vocabulary through the